The Pastoral Conversion of the Parish Community for the Asian Church - Yohanes Wahyu Rusmana (P3TK, Sanata Dharma University, 2021)
Discussions about parish institution today often end in its crisis. It seems that this institution is unable to carry out its functions in the modern world. On the other hand, so far, despite the emergence of new movements in the Church that are becoming the reference point in the life of some Christians, there is no institution that has replaced the parish yet. The parish remains a reference institution that shows the real face of the Church in society. On 20 July 2020, the Congregation for the Clergy published an instruction entitled “The pastoral conversion of the Parish community in the service of the evangelising mission of the Church”. This paper is an invitation to read and reflect on the pastoral conversion in parish life that focuses on the context of Asian Church priority to be a participatory Church and communion of communities. By applying the analytical method, we will examine the content of the instruction in confront with the context. In this way, finally we can find out the main points of how this instruction encourages pastoral conversion which should become the concern for the Asian Church. Therefore, this work helps us to understand better the importance of community conversion which means becoming a missionary community with the following two levels: all different parish communities that build up the entire parish and the parish community itself.